ICU Care in a Pandemic. Issue 6 (14th December 2021) - Prusak, Bernard; Gaurke, MaryKatherine; Jeong, Kyeong Yun; Scire, Emily; Sulmasy, Daniel P.
Abstract: This letter to the editor responds to commentaries in the September‐October 2021issue of the Hastings Center Report by Douglas B. White and Bernard Lo, by Govind Persad, and by Virginia A. Brown, which were themselves responding, in part, to the article "Life‐Years and Rationing in the Covid‐19 Pandemic: A Critical Analysis, " by MaryKatherine Gaurke, Bernard Prusak, Kyeong Yun Jeong, Emily Scire, and Daniel P. Sulmasy .